Peridynamic modelling and simulation of asphalt at low and high temperature. (27th February 2023) - Sanfilippo, D.; Ghiassi, B.; Alexiadis, A.
Highlights: X-ray Computer Tomography were employed to study the internal structure. The impact of the temperature and topology of voids on mechanical properties in asphalt mixtures was studied. Digital samples were created using the X-ray Computer Tomography scans. Peridynamic models have been used at −10 °C and 20 °C. Peridynamic model reproduces the asphalt mechanical properties and fracture characteristic at −10 °C and 20 °C. Abstract: Asphalt mixture undergoes damage caused by loading and environmental conditions. Understanding the degradation mechanisms may help design novel types of asphalt mixture. The laboratory tests, X-ray CT scans and computational analysis provide a complete assessment of the asphalt mixture's mechanical properties and fracture characteristics. In this study, the effect of temperature, aggregate, and void characteristics on the mechanical properties and fracture resistance are investigated, both experimentally and computationally. Three types of asphalt mixture are manufactured and X-rayed to acquire the internal structure of voids and aggregates. Asphalt mixture mechanical properties are determinate and correlated with aggregate and void and properties. Asphalt mixture has lower mechanical and fracture properties with higher void content and bigger aggregate. Irregular shapes (aspect ratio and circularity) of pores are detrimental to the asphalt mixture properties. CT scans are used to digitalize the asphalt mixtures samples before they are simulated with the peridynamics model. The model reproduces the asphalt mixture characteristic at −10 °C and 20 °C.